2009
DOI: 10.1029/2009gl039751
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Si and O between liquid iron and silicate melt: A two‐phase ab‐initio molecular dynamics study

Abstract: The magma ocean process in the early history of the Earth has a great influence on the light element identities and contents of the core which subsequently affect the energy of the geodynamo provided by the compositional convection and the inner core growth through their effect on the phase diagram of iron alloy. In the present work, a two‐phase ab‐initio molecular dynamics method is established to study the solubility of silicon and oxygen in liquid iron in equilibrium with silicate melt. The ab‐initio result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Properties of melts in the lower mantle are critical to understanding mantle chemical evolution, and theoretical and experimental studies have addressed issues of melt density and iron fractionation and Si and O partitioning between liquids and perovskite and ferropericlase in the deep mantle (e.g., de Koker and Stixrude, 2009;de Koker et al, 2013;Fiquet et al, 2010;Frost et al, 2004;Liebske and Frost, 2012;Mosenfelder et al, 2007;Seagle et al, 2008;Stixrude et al, 2009;Terasaki et al, 2007;Zhang and Fei, 2008;Zhang and Guo, 2009).…”
Section: Mineralogical Structurementioning
confidence: 99%
“…Properties of melts in the lower mantle are critical to understanding mantle chemical evolution, and theoretical and experimental studies have addressed issues of melt density and iron fractionation and Si and O partitioning between liquids and perovskite and ferropericlase in the deep mantle (e.g., de Koker and Stixrude, 2009;de Koker et al, 2013;Fiquet et al, 2010;Frost et al, 2004;Liebske and Frost, 2012;Mosenfelder et al, 2007;Seagle et al, 2008;Stixrude et al, 2009;Terasaki et al, 2007;Zhang and Fei, 2008;Zhang and Guo, 2009).…”
Section: Mineralogical Structurementioning
confidence: 99%
“…16) and is described only briefly here. Calculations are performed by using the ab-initio total-energy and molecular-dynamics program VASP (35).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we use the two-phase first-principles molecular dynamics (FPMD) method (16) to determine the partition coefficient of C and a few other light elements between liquid iron and silicate melt. This partition coefficient can then be combined with the composition of the bulk Earth or the primitive mantle (i.e., bulk silicate Earth) to infer the C content of the Earth's core.…”
mentioning
confidence: 99%
“…The ab initio calculations of Alfè et al ., [] indicate that O partitions strongly from the solid inner core into the liquid outer core, and, unlike Si, can explain observed density differences and seismic data. On the other hand, a two‐phase ab initio study of metal and silicate liquids has demonstrated that the partitioning of O into the Fe‐metal liquid is very limited, at least at 3100 K [ Zhang and Guo , ]. A high‐pressure experimental study using inelastic X‐ray scattering supports the presence of oxygen in the core [ Badro et al ., ], whereas an X‐ray diffraction study [ Sata et al ., ] precludes it.…”
Section: Introductionmentioning
confidence: 99%